Mixed-size diamond seeding for low-thermal-barrier growth of CVD diamond onto GaN and AlN. (15th October 2020) - Smith, E.J.W.; Piracha, A.H.; Field, D.; Pomeroy, J.W.; Mackenzie, G.R.; Abdallah, Z.; Massabuau, F.C.-P.; Hinz, A.M.; Wallis, D.J.; Oliver, R.A.; Kuball, M.; May, P.W.
Abstract: We report a method of growing a diamond layer via chemical vapour deposition (CVD) utilizing a mixture of microdiamond and nanodiamond seeding to give a low effective thermal boundary resistance (TBReff ) for heat-spreading applications in high-frequency, high-power electronic devices. CVD diamond was deposited onto thin layers of both GaN and AlN on Si substrates, comparing conventional nanodiamond seeding with a two-step process involving sequential seeding with microdiamond then nanodiamond. Thermal properties were determined using transient thermoreflectance (TTR), and the samples were also analysed with SEM and X-ray tomography. While diamond growth directly onto GaN proved to be unsuccessful due to poor adhesion, films grown on AlN were adherent and robust. The two-step mixed-seeding method gave TBReff values < 6 m 2  K GW −1 that were 30 times smaller than for films grown under identical conditions but using nanodiamond seeding alone. Such remarkably low thermal barriers obtained with the mixed-seeding process offer a promising route for fabrication of high-power GaN HEMTs using diamond as a heat spreader with an AlN interlayer. Graphical abstract: Image 1